2019
DOI: 10.1007/s00403-019-01975-0
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin type A suppresses pro-fibrotic effects via the JNK signaling pathway in hypertrophic scar fibroblasts

Abstract: Hypertrophic scar is a dermal fibroproliferative disease characterized by the overproduction and deposition of extracellular matrix, and the hyperproliferation and enhanced angiogenesis of fibroblasts, along with their enhanced differentiation to myofibroblasts. Botulinum toxin type A shows potential for prevention of hypertrophic scar formation; however, its effectiveness in attenuating skin fibrosis and the related mechanism are unclear. In this study, human scar fibroblasts were cultured and stimulated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 31 publications
(37 reference statements)
1
27
0
Order By: Relevance
“…Another possible target substance, which has shown similar regulating mechanisms, is botulinum toxin type A 51 . Its theoretical mechanism of action has been shown to be in an inhibition of TGF‐b1 as well as in an increase of the JNK phosphorylation leading to reduced fibroblast proliferation and production of profibrotic factors, among others 52 . No level of evidence I studies have investigated this substance to date.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible target substance, which has shown similar regulating mechanisms, is botulinum toxin type A 51 . Its theoretical mechanism of action has been shown to be in an inhibition of TGF‐b1 as well as in an increase of the JNK phosphorylation leading to reduced fibroblast proliferation and production of profibrotic factors, among others 52 . No level of evidence I studies have investigated this substance to date.…”
Section: Discussionmentioning
confidence: 99%
“…9 BTA has also been reported to suppress pro-fibrotic effects via the c-Jun N-terminal kinases (JNK) signaling pathway in hypertrophic scar fibroblasts in vitro. 10 However, the role of BTA on inhibiting HS formation through TGF-β1/Smad and MAPK pathways has not been determined. Therefore, the present study aimed to explore the potential mechanisms of BTA on the inhibition of HS formation.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that BTA can inhibit capsule formation through the TGF‐β1/Smad signaling pathway 9 . BTA has also been reported to suppress pro‐fibrotic effects via the c‐Jun N‐terminal kinases (JNK) signaling pathway in hypertrophic scar fibroblasts in vitro 10 . However, the role of BTA on inhibiting HS formation through TGF‐β1/Smad and MAPK pathways has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…lncRNA PAPPA-AS1 was picked out due to its high expression level in the HTsFb cells compared to NsFb. Fibroblasts are reported to be the main participants in the process and development of HTS by secreting collagens; the excessive proliferation of which is regarded as the main inducer for the formation of HTS [ 38 , 39 ]. Therefore, in the present study, HTsFb cells were taken as the study objects.…”
Section: Discussionmentioning
confidence: 99%